2017
DOI: 10.16970/entoted.297132
|View full text |Cite
|
Sign up to set email alerts
|

Biological parameters and population development of Tetranychus urticae Koch, 1836 (Acari: Tetranychidae) on different pepper cultivars

Abstract: SummaryPepper cultivar preferences of Tetranychus urticae Koch, 1836 (Acari: Tetranychidae) were determined by comparing its development, survival, oviposition, life table parameters and population development under controlled laboratory conditions with a 16L:8D photoperiod at 27±1ºC and 65±5% RH in Bursa (Turkey) during 2015-2016. Based on assays performed on leaf discs of six pepper cvs BT-Ince Sivri, BT-Burdem, BT-Burkalem, AHCRIÇarliston, AHCRI-Yağlık and AHCRI-Kandil Dolma, there were significant differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The immature developmental time was very similar with the values (9.1-11.2) reported by Khanamani et al (2013) on seven Indian eggplant cultivars. In addition, these durations are very close with previous studies performed on different suitable hosts in the same climatic condition: sweet pepper (11.7 days), cucumber (10.4 days), bean (10.9 days) and tomato (11.6 days) plants (Zatyko & Martinovich 1986;Kasap 2002;Razmjou et al 2009;Atalay & Kumral 2013;Kumral et al 2017). In the current study, a remarkable result is that the development durations of some eggplant cultivars are very close to bean values which are the most suitable host for T. urticae (Kasap 2002).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The immature developmental time was very similar with the values (9.1-11.2) reported by Khanamani et al (2013) on seven Indian eggplant cultivars. In addition, these durations are very close with previous studies performed on different suitable hosts in the same climatic condition: sweet pepper (11.7 days), cucumber (10.4 days), bean (10.9 days) and tomato (11.6 days) plants (Zatyko & Martinovich 1986;Kasap 2002;Razmjou et al 2009;Atalay & Kumral 2013;Kumral et al 2017). In the current study, a remarkable result is that the development durations of some eggplant cultivars are very close to bean values which are the most suitable host for T. urticae (Kasap 2002).…”
Section: Discussionsupporting
confidence: 89%
“…In the current study, the oviposition period was found as 9.42-16.85 days and the number of eggs per female was 45.50-71.14. These durations and values were determined as 5-13 days and 85-276 eggs for tomato; 24 days and 231 eggs for bean; 19 days and 124 eggs for soybean; 21 days and 172 eggs in cucumber; 7-13 days and 22-56 eggs for sweet pepper plants (Kasap 2002, Dehghan et al 2009, Razmjou et al 2009, Atalay & Kumral 2013Kumral et al 2017). Compared the most favourable host plants, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicated that the two-spotted spider mite does not accept all plants to the same degree (El-Sadan 2018). Many factors play an important role in plant acceptance (Kumral et. al., 2017).…”
Section: Introductionmentioning
confidence: 99%